Travelling Habits and Perceived Limitations of Older City Bus Users - Tomšič, Marija; Sevšek, France; Rugelj, Darja (Promet - Traffic&Transportation, 2017)
The purpose was to investigate the interrelation between the age of older city bus users, their travelling habits, their estimated physical (dis)abilities and perceived safety during the trip using the Ljubljana public transportation system. Methods: 101 older bus users agreed to participate in a street survey by answering a questionnaire. Results indicate that the habits of bus users are not age dependent. The frequency of public bus use, the walking distance to the nearest bus stop, the estimated physical abilities and perceived physical limitations of the bus users were not associated to the chronological age. Respondents reported on average 3±1.6 perceived physical limitations and 37% of them perceived their travelling habits to be affected by their physical limitations. While decreased perceived safety during the bus journey was significantly related to the chronological age: significantly more bus users of the oldest-old group reported not having enough time to occupy a seat before the bus drove off, although a significantly higher proportion of older-old adults were offered a seat by their fellow travellers. In conclusion, the perception of physical fitness and health problems are more important contributing factors for the use of public transportation than the chronological age.